Survival Benefit Associated With Resection of Locally Advanced Pancreatic Cancer After Upfront FOLFIRINOX Versus FOLFIRINOX Only: Multicenter Propensity Score-matched Analysis. Issue 5 (29th November 2021) - Brada, Lilly J. H.; Daamen, Lois A.; Magermans, Lisa G.; Walma, Marieke S.; Latifi, Diba; van Dam, Ronald M.; de Hingh, Ignace H.; Liem, Mike S. L.; de Meijer, Vincent E.; Patijn, Gijs A.; Festen, Sebastiaan; Stommel, Martijn W. J.; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: This study compared median OS after resection of LAPC after upfront FOLFIRINOX versus a propensity-score matched cohort of LAPC patients treated with FOLFIRINOX-only (ie, without resection). Background: Because the introduction of FOLFIRINOX chemotherapy, increased resection rates in LAPC patients have been reported, with improved OS. Some studies have also reported promising OS with FOLFIRINOX-only treatment in LAPC. Multicenter studies assessing the survival benefit associated with resection of LAPC versus patients treated with FOLFIRINOX-only are lacking. Methods: Patients with non-progressive LAPC after 4 cycles of FOLFIRINOX treatment, both with and without resection, were included from a prospective multicenter cohort in 16 centers (April 2015–December 2019). Cox regression analysis identified predictors for OS. One-to-one propensity score matching (PSM) was used to obtain a matched cohort of patients with and without resection. These patients were compared for OS. Results: Overall, 293 patients with LAPC were included, of whom 89 underwent a resection. Resection was associated with improved OS (24 vs 15 months, P < 0.01), as compared to patients without resection. Before PSM, resection, Charlson Comorbidity Index, and Response Evaluation Criteria in Solid Tumors (RECIST) response were predictors for OS. After PSM, resection remained associated with improved OS [Hazard Ratio (HR) 0.344, 95% confidence interval (0.222–0.534), P < 0.01], with an OS of 24 versus 15 months, as compared to patients without resection. Resection of LAPC was associated with improved 3-year OS (31% vs 11%, P < 0.01). Conclusions: Resection of LAPC after FOLFIRINOX was associated with increased OS and 3-year survival, as compared to propensity-score matched patients treated with FOLFIRINOX-only.